An integral approach to quantifying equivalent clean airflow rates of indoor air cleaning devices from pollutant injection and decay tests - Saman Haratian; Paul Dhununjay Claude Chittoo; P.S. Ganesh Subramanian; Vishal Verma; Mohammad Heidarinejad; Brent Stephens; Max Sherman (Building and Environment, 2025)

Predicting the impact of rare variants on RNA splicing in CAGI6 - Jenny Lord; Carolina Jaramillo Oquendo; Htoo A. Wai; Andrew G. L. Douglas; David J. Bunyan; Yaqiong Wang; Zhiqiang Hu; Zishuo Zeng; Daniel Danis; Panagiotis Katsonis; Amanda Williams; Olivier Lichtarge; et al. (Human Genetics, 2025)
Variants which disrupt splicing are a frequent cause of rare disease that have been under-ascertained clinically. Accurate and efficient methods to predict a variant’s impact on splicing are needed to interpret the growing number of variants of unknown significance (VUS) identified by exome and genome sequencing. Here, we present the results of the CAGI6 Splicing VUS challenge, which invited predictions of the splicing impact of 56 variants ascertained clinically and functionally validated to determine splicing impact. The performance of 12 prediction methods, along with SpliceAI and CADD, was compared on the 56 functionally validated variants. The maximum accuracy achieved was 82% from two different approaches, one weighting SpliceAI scores by minor allele frequency, and one applying the recently published Splicing Prediction Pipeline (SPiP). SPiP performed optimally in terms of sensitivity, while an ensemble method combining multiple prediction tools and information from databases exceeded all others for specificity. Several challenge methods equalled or exceeded the performance of SpliceAI, with ultimate choice of prediction method likely to depend on experimental or clinical aims. One quarter of the variants were incorrectly predicted by at least 50% of the methods, highlighting the need for further improvements to splicing prediction methods for successful clinical application.

High-resolution quadrupole improves spectral purity and reduces interference from non-target ions in isobaric multiplexed quantitative proteomics - Shen Zhang; J.C. Yves Le Blanc; Brett Larsen; Karen Colwill; Lyle Burton; Mircea Guna; Anne-Claude Gingras; Stephen Tate (Analytica Chimica Acta, 2024)

The paradox of high greenness and poor health in rural Central Appalachia - Jiaying Dong; Matthew H.E.M. Browning; Aaron Reuben; Olivia McAnirlin; Shuai Yuan; Claude Stephens; Mildred Maisonet; Kuiran Zhang; Jaime E. Hart; Peter James; Ray Yeager (Environmental Research, 2024)

High-precision Pb isotopes of drinking water lead pipes: Implications for human exposure to industrial Pb in the United States - George D. Kamenov; Benjamin F. Swaringen; David A. Cornwell; Nancy E. McTigue; Stephen M. Roberts; Jean-Claude J. Bonzongo (Science of The Total Environment, 2023)

Improved Segmentation of the Intracranial and Ventricular Volumes in Populations with Cerebrovascular Lesions and Atrophy Using 3D CNNs - Emmanuel E. Ntiri; Melissa F. Holmes; Parisa M. Forooshani; Joel Ramirez; Fuqiang Gao; Miracle Ozzoude; Sabrina Adamo; Christopher J. M. Scott; Dar Dowlatshahi; Jane M. Lawrence-Dewar; Donna Kwan; Anthony E. Lang; et al. (Neuroinformatics, 2021)

Improving African bean productivity in a changing global environment - Gebel Taba-Morales; Glenn Hyman; Jorge Rubiano Mejía; Fabio Castro-Llanos; Stephen Beebe; Jean Claude Rubyogo; Enid Katungi; Robin Buruchara (Mitigation and Adaptation Strategies for Global Change, 2020)

Electronic monitoring in fisheries: Lessons from global experiences and future opportunities - Aloysius T.M. van Helmond; Lars O. Mortensen; Kristian S. Plet‐Hansen; Clara Ulrich; Coby L. Needle; Daniel Oesterwind; Lotte Kindt‐Larsen; Thomas Catchpole; Stephen Mangi; Christopher Zimmermann; Hans Jakob Olesen; Nick Bailey; et al. (Fish and Fisheries, 2020)
Since the beginning of the 21st century, electronic monitoring (EM) has emerged as a cost‐efficient supplement to existing catch monitoring programmes in fisheries. An EM system consists of various activity sensors and cameras positioned on vessels to remotely record fishing activity and catches. The first objective of this review was to describe the state of play of EM in fisheries worldwide and to present the insights gained on this technology based on 100 EM trials and 12 fully implemented programmes. Despite its advantages, and its global use for monitoring, progresses in implementation in some important fishing regions are slow. Within this context, the second objective was to discuss more specifically the European experiences gained through 16 trials. Findings show that the three major benefits of EM were as follows: (a) cost‐efficiency, (b) the potential to provide more representative coverage of the fleet than any observer programme and (c) the enhanced registration of fishing activity and location. Electronic monitoring can incentivize better compliance and discard reduction, but the fishing managers and industry are often reluctant to its uptake. Improved understanding of the fisher's concerns, for example intrusion of privacy, liability and costs, and better exploration of EM benefits, for example increased traceability, sustainability claims and market access, may enhance implementation on a larger scale. In conclusion, EM as a monitoring tool embodies various solid strengths that are not diminished by its weaknesses. Electronic monitoring has the opportunity to be a powerful tool in the future monitoring of fisheries, particularly when integrated within existing monitoring programmes.

Age-related hearing loss increases full-brain connectivity while reversing directed signaling within the dorsal–ventral pathway for speech - Gavin M. Bidelman; Md Sultan Mahmud; Mohammed Yeasin; Dawei Shen; Stephen R. Arnott; Claude Alain (Brain Structure and Function, 2019)

Correction to: Genetic variant predictors of gene expression provide new insight into risk of colorectal cancer - Stephanie A. Bien; Yu-Ru Su; David V. Conti; Tabitha A. Harrison; Conghui Qu; Xingyi Guo; Yingchang Lu; Demetrius Albanes; Paul L. Auer; Barbara L. Banbury; Sonja I. Berndt; Stéphane Bézieau; et al. (Human Genetics, 2019)

Genetic variant predictors of gene expression provide new insight into risk of colorectal cancer - Stephanie A. Bien; Yu-Ru Su; David V. Conti; Tabitha A. Harrison; Conghui Qu; Xingyi Guo; Yingchang Lu; Demetrius Albanes; Paul L. Auer; Barbara L. Banbury; Sonja I. Berndt; Stéphane Bézieau; et al. (Human Genetics, 2019)

Monochamus species from different continents can be effectively detected with the same trapping protocol - Celia K. Boone; Jon Sweeney; Peter Silk; Cory Hughes; Reginald P. Webster; Fred Stephen; Lorraine Maclauchlan; Barbara Bentz; Alain Drumont; Boguang Zhao; Nick Berkvens; Hans Casteels; et al. (Journal of Pest Science, 2019)

Pan‐tropical prediction of forest structure from the largest trees - Jean‐François Bastin; Ervan Rutishauser; James R. Kellner; Sassan Saatchi; Raphael Pélissier; Bruno Hérault; Ferry Slik; Jan Bogaert; Charles De Cannière; Andrew R. Marshall; John Poulsen; Patricia Alvarez‐Loyayza; et al. (Global Ecology and Biogeography, 2018)
Aim Large tropical trees form the interface between ground and airborne observations, offering a unique opportunity to capture forest properties remotely and to investigate their variations on broad scales. However, despite rapid development of metrics to characterize the forest canopy from remotely sensed data, a gap remains between aerial and field inventories. To close this gap, we propose a new pan‐tropical model to predict plot‐level forest structure properties and biomass from only the largest trees. Location Pan‐tropical. Time period Early 21st century. Major taxa studied Woody plants. Methods Using a dataset of 867 plots distributed among 118 sites across the tropics, we tested the prediction of the quadratic mean diameter, basal area, Lorey's height, community wood density and aboveground biomass (AGB) from the i th largest trees. Results Measuring the largest trees in tropical forests enables unbiased predictions of plot‐ and site‐level forest structure. The 20 largest trees per hectare predicted quadratic mean diameter, basal area, Lorey's height, community wood density and AGB with 12, 16, 4, 4 and 17.7% of relative error, respectively. Most of the remaining error in biomass prediction is driven by differences in the proportion of total biomass held in medium‐sized trees (50–70 cm diameter at breast height), which shows some continental dependency, with American tropical forests presenting the highest proportion of total biomass in these intermediate‐diameter classes relative to other continents. Main conclusions Our approach provides new information on tropical forest structure and can be used to generate accurate field estimates of tropical forest carbon stocks to support the calibration and validation of current and forthcoming space missions. It will reduce the cost of field inventories and contribute to scientific understanding of tropical forest ecosystems and response to climate change.

A genome-wide association study for colorectal cancer identifies a risk locus in 14q23.1 - Mathieu Lemire; Conghui Qu; Lenora W. M. Loo; Syed H. E. Zaidi; Hansong Wang; Sonja I. Berndt; Stéphane Bézieau; Hermann Brenner; Peter T. Campbell; Andrew T. Chan; Jenny Chang-Claude; Mengmeng Du; et al. (Human Genetics, 2015)

Improving adaptation to drought stress in small red common bean: phenotypic differences and predicted genotypic effects on grain yield, yield components and harvest index - Teshale Assefa; Jixiang Wu; Stephen E. Beebe; Idupulapati M. Rao; Daniele Marcomin; Rubyogo J. Claude (Euphytica, 2015)

Meta-analysis of new genome-wide association studies of colorectal cancer risk - Ulrike Peters; Carolyn M. Hutter; Li Hsu; Fredrick R. Schumacher; David V. Conti; Christopher S. Carlson; Christopher K. Edlund; Robert W. Haile; Steven Gallinger; Brent W. Zanke; Mathieu Lemire; Jagadish Rangrej; et al. (Human Genetics, 2012)

Erratum to: Integration of microalgae cultivation with industrial waste remediation for biofuel and bioenergy production: opportunities and limitations - Patrick J. McGinn; Kathryn E. Dickinson; Shabana Bhatti; Jean-Claude Frigon; Serge R. Guiot; Stephen J. B. O’Leary (Photosynthesis Research, 2011)

Integration of microalgae cultivation with industrial waste remediation for biofuel and bioenergy production: opportunities and limitations - Patrick J. McGinn; Kathryn E. Dickinson; Shabana Bhatti; Jean-Claude Frigon; Serge R. Guiot; Stephen J. B. O’Leary (Photosynthesis Research, 2011)

Conditions for the arrest of a vertical propagating dyke - Benoît Taisne; Stephen Tait; Claude Jaupart (Bulletin of Volcanology, 2011)

A Child's View of Circulation in Prince William Sound, Alaska? - Stephen Okkonen; Claude Bélanger (Oceanography, 2008)

Restrictive and diversifying elements of the anti-myelin/oligodendrocyte glycoprotein antibody response in primate experimental allergic encephalomyelitis - H.-Christian von Büdingen; Til Menge; Stephen L. Hauser; Claude P. Genain (Immunogenetics, 2006)

Organization of the human liver carnitine palmitoyltransferase 1 gene (CPT1A) and identification of novel mutations in hypoketotic hypoglycaemia - Stéphanie Gobin; Jean-Paul Bonnefont; Carina Prip-Buus; Claude Mugnier; Magali Ferrec; France Demaugre; Jean-Marie Saudubray; Hidayeth Rostane; Fatima Djouadi; William Wilcox; Stephen Cederbaum; Richard Haas; et al. (Human Genetics, 2002)

Characterization of the expressed immunoglobulin IGHV repertoire in the New World marmoset Callithrix jacchus - Hans-Christian Büdingen; Stephen L. Hauser; Cameron B. Nabavi; Claude P. Genain (Immunogenetics, 2001)

Feeding, egg production, and egg hatching success of the copepods Acartia tonsa and Temora longicornis on diets of the toxic diatom Pseudo-nitzschia multiseries and the non-toxic diatom Pseudo-nitzschia pungens - Jean A. Lincoln; Jefferson T. Turner; Stephen S. Bates; Claude Léger; David A. Gauthier (Hydrobiologia, 2001)

Experimental test of the effect of ultraviolet‐B radiation in a planktonic community - Behzad Mostajir; Serge Demers; Stephen de Mora; Claude Belzile; Jean‐Pierre Chanut; Michel Gosselin; Suzanne Roy; Piedad Zulema Villegas; Juliette Fauchot; Josée Bouchard; David Bird; Patrick Monfort; et al. (Limnology and Oceanography, 1999)
Ultraviolet‐B (UVB, 280–320 nm) radiation is a natural component of sunlight that harms organisms and disturbs natural communities in surface waters. A natural planktonic assemblage of organisms (

QTL analysis to study the association between leaf size and abscisic acid accumulation in droughted rice leaves and comparisons across cereals - Stephen A. Quarrie; David A. Laurie; Jiahui Zhu; Claude Lebreton; Andrei Semikhodskii; Andrew Steed; Hanneke Witsenboer; Christina Calestani (Plant Molecular Biology, 1997)